Root traits and microbial community interactions in relation to phosphorus availability and acquisition, with particular reference to Brassica - Hunter, Paul J.; Teakle, Graham; Bending, Gary D. (Frontiers in Plant Science, 2014)
Brassicas are among the most widely grown and important crops worldwide. Phosphorus (P) is a key mineral element in the growth of all plants and is largely supplied as inorganic rock-phosphate, a dwindling resource, which is likely to be an increasingly significant factor in global agriculture. In order to develop crops which can abstract P from the soil, utilize it more efficiently, require less of it or obtain more from other sources such as soil organic P reservoirs, a detailed understanding the factors that influence P metabolism and cycling in plants and associated soil is required. This review focuses on the current state of understanding of root trait, rhizodeposition and rhizosphere community interaction as it applies to P solubilization and acquisition, with particular reference to Brassica species. Physical root characteristics, exudation of organic acids (particularly malate and citrate) and phosphatase enzymes are considered and the potential mechanisms of control of these responses to P deficiency examined. The influence of rhizodeposits on the development of the rhizosphere microbial community is discussed and the specific features of this community in response to P deficiency are considered; specifically production of phosphatases, phytases and phosphonate hydrolases. Finally various potential approaches for improving overall P use efficiency in Brassica production are discussed.